Memorandum re Shortage of Nurses - Labour Party (Great Britain). National Executive Committee ; Labour Party (Great Britain). Advisory Committee on Public Health ; Joint Research Dept. of the Trades Union Congress and the Labour Party; MacCallum, Maude
1924-07 1924 1920s 8 pages - 6 - (92) examinations too expensive ... the discipline was unnecessarily severe, and that he did not like a nurse to think she knew more than he did about his job ..." We fear many medical men prefer partly trained or partly educated nurses, lest they themselves should be criticised, but if medical men were half as loyal to nurses as nurses are to doctors, there could be no occasion for ill feeling. It is hard to suggest a means by which the attitude of the Medical profession may be altered, except by educating it up to the idea that nurses, as a matter of right and justice, should be self-governing, and we are of the opinion that their attitude is largely due to their hospital experience. When they see nurses over-worked and driven and bullied from morning to night, very often openly insulted in the wards before the patients by medical men, when they see them expected to open the door for them, and hold the towel while they wash their hands, how can students and young practitioners have much respect when they meet them in private practice? We think that the fountain-head of this trouble is the manner in which nurses are treated in hospital by those in authority, and are of the opinion that if a deputation could be arranged to wait on the British Medical Association, at which nurses could state plainly their grievances with regard to the medical profession, good might be accomplished. 3. Scarcity of Good Appointments after Nurses are Trained. After a nurse has received her three years' training, and fulfilled her fourth year of contract, she is then open to a post, and considered passing rich on £50 or £60 a year. Posts as matrons are naturally few and far between. In the Public Health Service nurses as superintendents of Welfare Centres are often superseded by medical women, so that being trained, there is small chance of promotion or of earning sufficient money to enable her to live decently and save for 292/842/1/14